Tradisi Khataman Al-Qur’an pada Bulan Suci Ramadhan di Kerinci (Sebuah Kajian Living Hadis) - Annisa Ulfitri (Al-Manar: Jurnal Kajian Alquran dan Hadis, 2023)
This study describes the living hadith in the tradition of khataman al-Qur'an during the holy month of Ramadan in Koto Petai Village. This research is qualitative research using the analytical description method. The object of this research is the Khataman Al-Qur'an Tradition during Ramadan in Koto Petai, Kerinci, Jambi. Based on this research, it was found that the tradition of khataman al-Qur'an in the holy month of Ramadan in Koto Petai Village is classified as a study of living hadith. This is marked by the khataman phenomenon, which is part of the tradition of presenting and actualizing hadiths amid the life of the Muslim community in Koto Petai Village. The community's reception of the khataman al-Qur'an is to motivate people to be able to read the al-Quran well because other people listen to their readings. Besides that, if group members, children, or in-laws cannot read the Koran, they will be found out, thus forcing them to learn to read the Qur'an.